Pengelolaan ZIS Berbasis Komunitas untuk Mengurangi Ketimpangan Sosial: Studi Kasus Kamrat Kifaya di Pedesaan Madura - Rafiqi, Iqbal (Al-Amien Prenduan for Islamic Institute, 2025)
Social inequality and poverty remain persistent issues in Indonesia, with over 25.89 million people affected. While formal zakat institutions are widely recognized, this study explores the Kamrat Kifayah, a grassroots, community-driven initiative in Larangan Luar Pamekasan Madura, that has operated since the 1970s without formal legal status. Rooted in social capital and Islamic values, Kamrat Kifaya organizes regular religious gatherings (e.g., Yasin recitations and tahlil) and collects Zakat, Infaq, and Sadaqah (ZIS) to support bereaved families. Using a qualitative case study approach, this research collected data through interviews with Kamrat leaders and members, as well as field observations and documentation analysis. The findings reveal Kamrat Kifaya’s significant contribution to social solidarity and informal safety nets. The SWOT analysis shows strengths in longevity and trust, with social acceptance across diverse groups; weaknesses in limited ZIS allocation (primarily for death-related needs); opportunities in fund diversification for small businesses; and threats in conventional management methods. This study highlights the potential of integrating local wisdom-based ZIS models with broader Islamic economic frameworks. It contributes to the discourse on community-based philanthropy and offers a practical alternative for inclusive ZIS empowerment in rural Muslim societies.